Teachers' Professional Development Through The Smart Model: Teachers' Lived Experiences in Madrasah Setting - Hesty Widiastuty; Zaitun Qamariah; Moc Chotib; Ahmadi; Harmini; Ummi Qudsiyah; Salasiah (Mudir: Jurnal Manajemen Pendidikan, 2025)
This phenomenological study explores madrasah teachers' experiences implementing the SMART Model (Support, Motivation, Assessment, Reward, and Training) in teacher management at MTs Terpadu Berkah, Palangka Raya. Data were collected through in-depth interviews with 15 purposively selected participant, including the principal, vice-principals, and selected teachers, observations (20 hours), and document analysis. The findings reveal that the SMART Model enhances teacher professionalism through systematic support mechanisms, targeted motivation strategies, comprehensive performance assessments, structured reward systems, and sustainable professional development opportunities. However, challenges such as resource constraints, inconsistent implementation, and communication barriers limit its effectiveness. The study contributes to educational management literature by proposing a context-specific framework for teacher management in Islamic educational institutions and recommends optimizing performance-based evaluations and reward systems to improve educational quality in madrasahs. This research underscores the significance of integrating SMART Model components to foster a more supportive and motivating environment for teachers in Islamic educational settings.